Effect of cosmetic outcome on quality of life after breast cancer surgery. Issue 3 (March 2015) - Kim, M.K.; Kim, T.; Moon, H.G.; Jin, U.S.; Kim, K.; Kim, J.; Lee, J.W.; Kim, J.; Lee, E.; Yoo, T.K.; Noh, D.-Y.; Minn, K.W.; et al.
Abstract Purpose Studies regarding the effects of aesthetic outcomes after breast cancer surgery on quality of life (QoL) have yielded inconsistent results. This study analyzed the aesthetic outcomes and QoL of women who underwent breast conserving surgery (BCS) or total mastectomy with immediate reconstruction (TMIR) using objective and validated methods. Patients and methods QoL questionnaires (EORTC QLQ-C30, BR23, and HADs) were administered at least 1 year after surgery and adjuvant therapy to 485 patients who underwent BCS, 46 who underwent TMIR, and 87 who underwent total mastectomy (TM) without reconstruction. Aesthetic results were evaluated using BCCT.core software and by a panel of physicians. Patients' body image perception was assessed using the body image scale (BIS). Results QoL outcomes, including for social and role functioning, fatigue, pain, body image, and arm symptoms, were significantly better in the BCS and TMIR groups than in the TM group (p<0.05 each). BIS was significantly better in the BCS than in the TM or TMIR group (p<0.001 each). In the BCS and TMIR groups, general QoL factors were not significantly associated with objective cosmetic outcomes, except for body image in the QLQ-BR23. In contrast, patients with poorer BIS score reported lower QoL in almost all items of the QLQ-C30, BR23, and HADS (p<0.05 each). Conclusion In conclusion, BCS and TMIR enhanced QoL compared with TM. Among BCS and TMIR patients, objectively measured cosmetic results did not affect general QoL. Self-perception of body image seems to be more important for QoL after breast cancer surgery.